The story of Bentong Kali crime and society in 90s Kuala Lumpur - Suganthi Suparmaniam (Gerakbudaya Enterprise, 2019)
The Story of Bentong Kali details the rise and fall of one of Malaysia's most notorious gangsters Kalimuthu a/l Pakirisamy, better known as Bentong Kali, who terrorised the nation in the early 1990s. On the front of every newspaper, he was believed to be behind at least 16 murders and attempted murders before being killed by police in a double-storey house in Medan Damansara alongside two of his accomplices S. Gunalan aka Billiard and T. Gunasegaran aka Raub Guna. Written by journalist Suganthi Suparmaniam, The Story of Bentong Kali traces Kalimuthu's journey from his poor childhood in Bentong, Pahang to the streets of KL where he became involved in the drugs trade and protection work before forming his own gang and amassing around him a group of loyal followers. Based on first-hand interviews with former gang members, family members, police, including Tan Sri Zaman Khan, and journalists who covered the case, The Story of Bentong Kali gives an in depth account of the life of Kalimuthu and the events that led to a crime spree which captivated the nation. It tells the story not only of one gangster but also of a rapidly developing society coming to terms with problems of crime, drugs and economic insecurity.